Paradoxical Effect of Cardiac Output on Arterial Enhancement at Computed Tomography: Does Cardiac Output Reduction Simply Result in an Increase in Aortic Peak Enhancement?. Issue 3 (May 2017) - Kidoh, Masafumi; Nakaura, Takeshi; Funama, Yoshinori; Shimonobo, Toshiaki; Shirasaka, Takashi; Hatemura, Masahiro; Utsunomiya, Daisuke; Oda, Seitaro; Yuki, Hideaki; Namimoto, Tomohiro; Higaki, Toru; Awai, Kazuo; et al.
Abstract : Objective: The aim of this study was to evaluate the effect of cardiac output (CO) on aortic peak enhancement using protocols with different contrast material (CM) injection durations. Methods: We used a flow phantom that simulated the human circulatory system. Contrast material was injected at a rate of 4.0 mL/s for a period of 2.5, 5, 10, 15, or 20 seconds for a CO of 2.8, 4.2, and 5.6 L/min. Single-level serial computed tomography scans of the simulated aorta were acquired after the start of CM delivery, and aortic peak enhancement was recorded under the different injection protocols. Results: Under a long injection duration protocol (20 seconds), a decrease in CO increased aortic peak enhancement proportionally (CO of 2.8 L/min, 420 Hounsfield units [HU]; CO of 4.2 L/min, 365 HU; CO of 5.6 L/min, 291 HU). However, this effect was decreased under shorter injection duration protocols (5, 10, and 15 seconds); under the shortest (2.5-second) injection duration protocol, a decrease in CO resulted in a decrease in aortic peak enhancement (CO of 2.8 L/min, 36 HU; CO of 4.2 L/min, 51 HU; CO of 5.6 L/min, 55 HU). Conclusions: The magnitude of the effect of CO on aortic peak enhancement depends on the CM injection duration.